2017
DOI: 10.1186/s12931-017-0532-y
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of CD14 haplotypes and soluble CD14 on pulmonary function in agricultural workers

Abstract: BackgroundAgricultural environments are contaminated with organic dusts containing bacterial components. Chronic inhalation of organic dusts is implicated in respiratory diseases. CD14 is a critical receptor for gram-negative lipopolysaccharide; however, its association with respiratory disease among agricultural workers is unknown. The objective of this study was to determine if serum soluble CD14 (sCD14) levels are associated with lung function among agricultural workers and if this association is modified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…Membrane-bound CD14 is primarily made by monocytes, macrophages and granulocytes [15]. It is not normally found in endothelial or epithelial cells, such as the ones used in our study, which may instead depend on sCD14 for TLR4 activation [13]. A previous study indicated that serum is a key component of LPS activation (versus serum-free media) and that in the absence of serum, direct addition of CD14 (also found in serum) is sufficient for LPS stimulation of IL-8 production [3].…”
Section: Higher Serum Concentration Improves Lps Sensitizationmentioning
confidence: 75%
See 1 more Smart Citation
“…Membrane-bound CD14 is primarily made by monocytes, macrophages and granulocytes [15]. It is not normally found in endothelial or epithelial cells, such as the ones used in our study, which may instead depend on sCD14 for TLR4 activation [13]. A previous study indicated that serum is a key component of LPS activation (versus serum-free media) and that in the absence of serum, direct addition of CD14 (also found in serum) is sufficient for LPS stimulation of IL-8 production [3].…”
Section: Higher Serum Concentration Improves Lps Sensitizationmentioning
confidence: 75%
“…According to established literature on LPS stimulation, the efficiency of TLR4 activation by LPS is greatly increased by LPS-binding protein and CD14 [12][13][14]. CD14 is expressed as both a phosphatidylinositol-linked membrane-bound form (mCD14) and as a soluble circulating form (sCD14) [13]. Membrane-bound CD14 is primarily made by monocytes, macrophages and granulocytes [15].…”
Section: Higher Serum Concentration Improves Lps Sensitizationmentioning
confidence: 99%
“…В одному з досліджень встановлено, що при загостреннях ХОЗЛ відбувається підвищення sCD14 у крові -молекули, яка асоціюється зі старшим віком, жіночою статтю, поточним статусом куріння, гіпертензією, тригліцеридами, СРБ та ЦД2 [18,19]. Проте в роботі Shitole SG зазначається про відсутність зв'язку з ЦД2 [20].…”
unclassified